2023
DOI: 10.1177/00469580221146826
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Cultural Adaption and Validation of SERVPERF Tool for Measuring Healthcare Quality in an Oncology Public Hospital, Vietnam

Abstract: SERVPERF (Service Performance) tool needs to be adapted to the context and the usage purpose. Our study aimed to validate the context adapted SERVPERF tool in an Oncology public hospital in Vietnam. A study was conducted in 2020 with 227 in-patients as respondents the modified SERVPERF tool. Data collected were analyzed for tool assessment (reliability and validity). The new order in 5 factors in the modified tool were: (1) Responsiveness; (2) Empathy; (3) Reliability; (4) Tangible and (5) Assurance. The modif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…All items use a five-point Likertscale with strongly disagree, disagree, neither disagree nor agree, agree and strongly agree (see online appendix for the SERVQUAL scales). Measures of perceived level of service performance were appropriate to measure service quality [8] and had a high predictive validity for satisfaction. [17] These 15 items are clustered into five dimensions: assurance, responsiveness, reliability, empathy, and tangible service quality.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…All items use a five-point Likertscale with strongly disagree, disagree, neither disagree nor agree, agree and strongly agree (see online appendix for the SERVQUAL scales). Measures of perceived level of service performance were appropriate to measure service quality [8] and had a high predictive validity for satisfaction. [17] These 15 items are clustered into five dimensions: assurance, responsiveness, reliability, empathy, and tangible service quality.…”
Section: Methodsmentioning
confidence: 99%
“…[6] Furthermore, patient perceptions of service quality in emerging countries frequently rely on data from public hospitals. [7,8] This paper addresses these gaps by developing a robust, contextualised and validated measurement model for assessing data from both public and private health facilities in Romania (the second largest new member state among CEECs). Furthermore, unlike prior studies that have assessed the impact of individual service quality attributes on patients' perceptions of overall healthcare services, [9,10] this paper addresses the distinct paucity of research on patient service attribute perceptions associated with different types of healthcare services offered, e.g., primary care, ambulatory care, and inpatient care.…”
Section: Introductionmentioning
confidence: 99%
“…In the literature there are many theoretical models that refer to the quality approach as a method of measuring customer satisfaction. Some refer to cases of application to measuring citizen satisfaction in the public sector [50][51][52][53][54], the SERVQUAL model [13,[55][56], the SERVPERF model [57][58]. In this research, the SERVPERF model of Cronin and Taylor [59] was chosen who held a different perspective on using the CQA (Customer Questionnaire Approach) to assess service quality.…”
Section: Measuring Ict Services In Public Sectormentioning
confidence: 99%
“…It was reported that the suggested approach enhanced the decision-making process, increasing the effectiveness of the operation of the surgical center. Duc Thanh et al [36] proposed a service performance tool to measure the service quality in an oncology public hospital in Vietnam.…”
Section: Literature Reviewmentioning
confidence: 99%